Dążenia kobiet do dostępu do edukacji akademickiej na ziemiach polskich na przełomie XIX i XX wieku - Pawlicka, Natalia (Biuletyn Historii Wychowania, 2023)
The purpose of the article is to present women’s aspirations for access to academic education in Poland at the turn of the 19th and 20th centuries. Educational inequalities accompanied women at all levels of education. However, the biggest problems were encountered by women in pursuit of tertiary education. It was this path of development that was inaccessible to them for the longest time in Poland. The difficult economic situation of Poles during the Partitions over time forced the society to slowly change the thinking and approach to the academic and professional activity of women. Due to the lack of opportunities to study in the partitioned area, the only possibility for Polish women to study at a higher level was academic emigration. The most common destinations were Switzerland, France, and, in the last decade of the 19th century, also Belgium. The beginnings of the practical struggle for access to tertiary education by women date back to 1892–1910. At this time, emancipation associations were involved in petitioning university authorities to grant women permission to study. This article is an attempt to trace the educational possibilities of women in Poland, with special emphasis placed on women’s aspirations to access academic education at the turn of the 19th and 20th centuries. The article uses the methods of historical and pedagogical research and text analysis.